The Influence Of Professional Learning Communities, Teachers Collaboration And Empowerment On The Teaching Effectiveness In The Maldives - Nasir, Mohamed (2024)
This research specifically explores i) the role of teacher collaboration on teacher teaching effectiveness ii) the role of teacher empowerment on teaching effectiveness iii) the influence of professional learning communities, collaboration and empowerment on teacher teaching effectiveness in the Maldives